2016
DOI: 10.17511/ijpr.2016.i05.04
|View full text |Cite
|
Sign up to set email alerts
|

To study the effectiveness of indigenous bubble CPAP in management of respiratory distress in newborns

Abstract: Background: CPAP has become a useful in management of respiratory distress, especially in preterms. CPAP delivers a continuous distending pressure via the neonates pharynx to the upper and lower airways. The main indication for use of CPAP is RDS. Aim of study: To study the effectiveness of indigenous bubble CPAP in management of respiratory distress in newborn and to determine its outcome. Setting: Department of Pediatrics, MGM Medical College and MY Hospital, Indore during the period February-July 2005. Desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 2 publications
2
4
0
Order By: Relevance
“…8% and CHD 2%. Other observation was 72% of meconium aspiration syndrome babies put on bubble CPAP survived which was similar to observation done by Jain H et al [7] Out of 100 cases 73% improved, 21% further required mechanical ventilation and 6% were discharge against medical advise. Regarding the outcome of CPAP, many studies have shown lower mortality and morbidity rate in infants with birth weight greater than 1500 gm who were put on CPAP compared to those managed on mechanical ventilation.…”
Section: Talawar Et Al; Indigenous Bubble Cpap In Neonates With Respisupporting
confidence: 81%
See 1 more Smart Citation
“…8% and CHD 2%. Other observation was 72% of meconium aspiration syndrome babies put on bubble CPAP survived which was similar to observation done by Jain H et al [7] Out of 100 cases 73% improved, 21% further required mechanical ventilation and 6% were discharge against medical advise. Regarding the outcome of CPAP, many studies have shown lower mortality and morbidity rate in infants with birth weight greater than 1500 gm who were put on CPAP compared to those managed on mechanical ventilation.…”
Section: Talawar Et Al; Indigenous Bubble Cpap In Neonates With Respisupporting
confidence: 81%
“…This study demonstrates the potential impact of introducing a low cost, appropriate bubble CPAP system. The low cost indigenous bubble CPAP system we used was almost similar to that used in other studies by Charanjit Kaur et al, [5] Shrestha et al, [6] Pooniya V et al, [4] Jain H et al [7] In our study common indication for bubble CPAP was respiratory distress syndrome 32%, followed by birth asphyxia 28%, MAS 11%, TTNB 8%, apnea of prematurity…”
Section: Discussionsupporting
confidence: 57%
“…In our study, the survival rate was 72.9 % in B-CPAP group and 75.7% in I-CPAP group. 6,15 Thus, I-CPAP has similar survival rates as compared to B-CPAP. The complications, such as, culture proven sepsis (22.9% in B-CPAP versus 12.12% in I-CPAP) and NSD (47.9% in B-CPAP vs 6% in I-CPAP, p value 0.000062) were comparable to another recent study.…”
Section: Discussionmentioning
confidence: 96%
“…4500-8000) can prove to be effective and non-invasive way to provide ventilation to patients of RDS in a setup with limited resources. 6,7 It can be used as a delivery room CPAP at peripheral health centres and for transport of new-borns to tertiary care hospital.…”
Section: Introductionmentioning
confidence: 99%
“…recent study in this issue by Jain H et al highlighted that indigenous bCPAP is an effective and non-invasive way to provide ventilation in a setup with limited resources. It can be used to manage respiratory distress ISSN 2349-5499 Editorial Pediatric Review: International Journal of Pediatric Research Available online at: www.pediatricreview.in due to RDS, congenital pneumonia & meconium aspiration syndrome[8].…”
mentioning
confidence: 99%